Digitalizing consumer society: equipment and devices of digital consumption. Issue 1 (2nd January 2020) - Cochoy, Franck; Licoppe, Christian; McIntyre, Magdalena Petersson; Sörum, Niklas
ABSTRACT: This special issue of the Journal of Cultural Economy focuses on the digitalization of consumption and its social, cultural, ethical, political, and gendered implications. It thus answers the call for more research on how digital devices spread from the purely personal domain to multiple sociocultural domains. Through their use, new cultural practices have emerged between consumers and these devices, and devices and markets, that lead to change, in terms of consumer demand, consumption norms, and issues of ethics, culture, and power. Closely examining the role that devices play in consumption behavior enables us to address the supposed manipulative power of hi-tech companies, infrastructures, and systems at the global level, and the view ordinary market actors hold of digital appliances as empowering tools at the local level. The papers in this volume bridge 'actor network theory' and 'consumer culture theory' from the perspective of market 'agencements.' Ruckenstein-Granroth and Beauvisage-Mellet, and Arriagada-Concha focus on the device-mediated relationship between large digital market infrastructures and consumer behavior; Petersson McIntyre and Licoppe unveil the societal and cultural underpinnings of digitalized markets. Last but not least, Sörum and Soujtis address the political dimensions and implications of our new digital consumer equipment and society.